Structural Features and Immunomodulatory Effects of Water-Extractable Polysaccharides from Macrolepiota procera (Scop.) Singer - Georgiev, Yordan Nikolaev; Vasicek, Ondrej; Dzhambazov, Balik; Batsalova, Tsvetelina Georgieva; Denev, Petko Nedyalkov; Dobreva, Lili Ivaylova; Danova, Svetla Trifonova; Simova, Svetlana Dimitrova; Wold, Christian Winther; Ognyanov, Manol Hristov; Paulsen, Berit Smestad; Krastanov, Albert Ivanov (Journal of fungi (Basel, Switzerland), 2022)
Macrolepiota procera (MP) is an edible mushroom used in the treatment of diabetes, hypertension and inflammation. However, the structure and biological effects of its polysaccharides (PSs) are unclear. This study investigates the structural features of a PS complex from MP (MP-PSC), its immunomodulatory activities and effects on probiotic and pathogenic bacteria. MP-PSC was obtained by boiling water, and PSs were characterized by 2D NMR spectroscopy. The immunomodulatory effects on blood and derived neutrophils, other leukocytes, and murine macrophages were studied by flow cytometry, chemiluminescence, spectrophotometry, and ELISA. The total carbohydrate content of MP-PSC was 74.2%, with glycogen occupying 36.7%, followed by β-D-glucan, α-L-fuco-2-(1,6)-D-galactan, and β-D-glucomannan. MP-PSC (200 μg/mL) increased the number of CD14+ monocyte cells in the blood, after ex vivo incubation for 24 h. It dose-dependently (50-200 μg/mL) activated the spontaneous oxidative burst of whole blood phagocytes, NO, and interleukin 6 productions in RAW264.7 cells. MP-PSC exhibited a low antioxidant activity and failed to suppress the oxidative burst and NO generation, induced by inflammatory agents. It (2.0%, w/v) stimulated probiotic co-cultures and hindered the growth and biofilm development of Escherichia coli, Streptococcus mutans and Salmonella enterica. MP PSs can be included in synbiotics to test their immunostimulating effects on compromised immune systems and gut health.
Keywords: inflammation; probiotic bacteria; Escherichia coli; biofilm; prebiotic activity; NMR; immunomodulatory activity; polysaccharides; Clostridium beijerinckii; Macrolepiota procera